Perlindungan Hukum Pemilik Sertipikat Lama Dalam Transformasi Digital Badan Pertanahan Nasional - Arif Fathu Rohman; Muhammad Fadli (Universitas Sains dan Teknologi Komputer, 2026)
This study examines the legal protection afforded to holders of conventional land certificates amid the digital transformation of land administration in Indonesia, particularly following the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency's implementation of electronic land documents. The study is motivated by continuing agrarian disputes, legal uncertainty, and public concerns regarding the security of digital land data, including risks of data alteration, administrative failure, and cyber intrusion. Using a normative juridical approach, this research analyzes statutory regulations, legal doctrines, and related legal materials concerning land registration and electronic certification. The findings indicate that conventional land certificates remain legally valid and retain evidentiary force during the transition to electronic certification. However, the transition has not yet been supported by fully coherent legal and administrative safeguards, particularly regarding historical data accuracy, system reliability, and protection against digital vulnerabilities. This condition creates a degree of legal uncertainty for owners of older certificates, especially those with limited access to information and digital services. The study concludes that stronger legal protection requires not only regulatory harmonization but also gradual implementation, institutional readiness, data security assurance, and broader public legal education to ensure that digital transformation in land administration promotes legal certainty, justice, and equitable access for all land rights holders.